The relationship of the distribution of ROH in the genome of Russian snow-white chickens with productive and adaptive traits, depending on the direction of selection - E. S. Fedorova; N. V. Dementieva; O. I. Stanishevskaya; A. E. Ryabova (Аграрная наука Евро-Северо-Востока)
In recent years, increasing attention has been paid to the problem of preserving the genetic diversity of farm animals and poultry. However, an indispensable condition for the economic feasibility of preserving any breed is not only its uniqueness, but also the possibility of practical use. An example is the Russian snow-white breed of chickens in the VNIIGRZh bioresource collection. It was developed by breeding of Russian white chickens for thermal resistance at low temperature conditions, as well as for resistance to neoplastic diseases. Currently, this breed is specialized for the purposes of the bio-industry (raw materials for the production of embryonic viral vaccines). The change in the direction of breeding work led to a modification of the genetic structure of the population. Constant selective pressure on one particular trait can lead to a decrease in variability around the genomic regions associated with that trait. Therefore, understanding the genetic mechanisms leading to phenotypic differentiation requires the identification of regions in the genome that were under selection pressure. The study of runs of  homozygosity (ROH) rates can provide useful information about the history of population selection, as well as allow for a better understanding of the genotype-phenotype relationship by discovering genes that are or were under selection pressure. In ROH islands specific to two generations of chickens, the most relevant candidate genes associated with adaptive traits are annotated. It has been established that genetic analysis based on changes in ROH can be used to characterize the genetic profile of chickens and to change the structure of the population under the influence of selection pressure. These data are especially important to take into account when evaluating qualitative phenotypic features, such as the adaptive capabilities of chickens.